Sex Chromosome Dosage Compensation in Insects - Xingcheng Xie; Yakun Zhang; Heyuan Peng; Zhongyuan Deng (Insects)
Dosage compensation (DC) is of crucial importance in balancing the sex-linked gene expression between males and females. It serves to guarantee that the proteins or other enzymatic products encoded by the sex chromosome exhibit quantitative parity between the two genders. During the evolutionary process of achieving dose compensation, insects have developed a wide variety of mechanisms. There exist two primary modes of dosage compensation mechanisms, including the up-regulation of heterogametic sex chromosomes in the heterogamety and down-regulation of homogametic sex chromosomes in the homogamety. Although extensive investigations have been conducted on dosage compensation in model insects, many questions still remain unresolved. Meanwhile, research on non-model insects is attracting increasing attention. This paper systematically summarizes the current advances in the field of insect dosage compensation with respect to its types and mechanisms. The principal insects involved in this study include the Drosophila melanogaster, Tribolium castaneum, Bombyx mori, and other lepidopteran insects. This paper analyzes the controversial issues about insect dosage compensation and also provides prospects for future research.